How to Say Things with Words: Ways of Saying in English and Spanish - Rojo, Ana; Valenzuela, Javier (Meta, 2001)
AbstractSlobin (1997, 1998) has pointed out the differences between Spanish and English verbs of motion with regard to the expression of elements such as “Path of motion” or “Manner of motion”. Generally speaking, English verbs incorporate manner to their core meaning while Spanish verbs tend to incorporate Path, expressing Manner with an additional complement. Comparing English motion events and their translation into Spanish in several novels, Slobin found out that only 51% of English manner verbs were translated into Spanish manner verbs (Slobin 1996), the rest being neutralized or omitted. We intend to apply Slobin's analysis to verbs of saying in English and Spanish. Our work aims to analyze the conflation patterns of verbs of saying in English and Spanish and the way Spanish translators deal with them.